Evaluation of Structural Performance of Single Layer Steel Space Lattice Dome Systems - Hayalioğlu, M. Sedat; Bektaş, Mehmet Ali (Fırat University, 2024)
Steel dome systems are roof covering systems with wide spans that require minimum number of load-bearing elements. Single layer dome systems which is the one of these dome systems, exhibit a different structural performance due to their geometric and design features. Therefore, we need to understand correctly the stress distribution and design the systems accordingly. This article presents the results of a study on the analysis and design of a single-layer steel space lattice dome system. Based on the Eurocode-1 and Turkish Building Earthquake Code 2018, the calculations of the loads acting on the structure and the desings in accordance with the AISC 360-10 regulations were carried out, and then, the cross-sections of the bars with critical stresses were checked according to the Turkish steel structure regulations. The findings show that the circle beams of the dome system have the highest tensile stresses in the skirt regions and the highest compressive stresses in the apex regions, and that the bars can be subjected to different stresses under asymmetrical loads. In addition, it has been observed that AISC 360-10 and Turkish steel structure regulations give very close and similar results. This study is an important guide for engineers dealing with single-layer dome systems, emphasizing that tensile and compressive stresses arising from dome geometry should be taken into account in structural design.

Çelik kubbe sistemleri, geniş açıklıkları en az taşıyıcı eleman gereksinimi duyarak yapılan çatı örtü sistemleridir. Bu kubbe sistemlerinden biri olan tek katmanlı kubbe sistemleri, geometrik ve tasarımsal özelliklerinden dolayı farklı bir yapısal performans sergilemektedirler. Bu nedenle, gerilme dağılımını doğru bir şekilde anlamamız ve tasarımı buna göre yapmamız gerekmektedir. Bu makalede, tek katmanlı çelik uzay kafes kubbe sisteminin analizi ve tasarımı üzerine yapılan bir çalışmanın sonuçları sunulmaktadır. Eurocode-1 ve Türkiye Bina Deprem Yönetmeliği 2018 esas alınarak yapıya etki eden yüklerin hesaplamaları ve AISC 360-10 yönetmeliğine uygun boyutlandırmalar gerçekleştirilmiştir. Daha sonra kritik gerilme oluşan çubukların kesit kontrolleri Çelik Yapıların Tasarım, Hesap ve Yapım Esaslarına Dair Yönetmeliğine göre kontrol edilmiştir. Bulgular, kubbe sisteminin çember kirişlerinin etek bölgelerinde en yüksek çekme, tepe bölgelerinde ise en yüksek basınç gerilmelerine sahip olduğunu ve asimetrik yük altında çubukların farklı gerilmelere maruz kalabileceğini göstermektedir. Ayrıca AISC 360-10 ile Çelik Yapıların Tasarım, Hesap ve Yapım Esaslarına Dair Yönetmeliğinin birbirine çok yakın ve benzer sonuçlar verdiği görülmüştür. Bu çalışma, tek katmanlı kubbe sistemleriyle ilgilenen mühendisler için önemli bir rehber niteliği taşımakta olup, yapı tasarımında kubbe geometrisinden kaynaklanan çekme ve basınç gerilmelerinin göz önünde bulundurulması gerektiğini vurgulamaktadır.
Tek Katmanlı Çelik Uzay Kafes Kubbe Sistemlerinin Yapısal Performansının İncelenmesi
Keywords: Structural Engineering; Yapı Mühendisliği